Relasi Studi Islam Pendekatan MIT dan Nalar Kitab Kuning MUFADA Mahasiswa: Telaah Fenomenologis-Antropologis - Fauzi, Moh Nur; Junadi, Syafi'; Manshur, Ali; Lestari, M Budi (JURNAL ISLAM NUSANTARA, 2022)
This study aims to unravel the relationship between Multidisciplinary Interdisciplinary Transdisciplinary Islamic studies and the study of the yellow book of IAI Darussalam Banyuwangi students who are members of the MUFADA institution. MUFADA is a forum for students and students of IAI Darussalam who concentrate on understanding the yellow book and are active in various places in society. MUFADA is an interesting religious phenomenon to study because it is an institution that gives voice to the students in responding to conditions in the current era. This research is qualitative in nature and uses interviews, observation and literature studies. The approach used is phenomenological-anthropological by focusing on several important points, first, how IAI Darussalam students approach understanding the yellow book; second, how is the relationship between MIT's approach to the study of the yellow book at the MUFADA institution; third, how is the phenomenological-anthropological relationship between MUFADA and IAI Darussalam, Islamic Boarding Schools, and the Community. The results of this study indicate that the approach used by IAI Darussalam (MUFADA) students in understanding the yellow book is contextual and relational with various approaches to modern social science which is appreciated at the IAI Darussalam college.